Comparative study of robotic-assisted vs. laparoscopic surgery for colorectal cancer: a single-center experience - Wang, Wenpeng; Liu, Jia; Wang, Jiefu; Li, Li; Kong, Dalu; Wang, Junfeng (Frontiers in Oncology, 2025)
BackgroundColorectal cancer (CRC) surgeries are commonly performed using either robotic-assisted colorectal surgery (RACS) or laparoscopic colorectal surgery (LCS). This study aimed to compare clinical and surgical outcomes between RACS and LCS for CRC patients.MethodsWe included 225 patients from Tianjin Medical University Cancer Institute & Hospital (TJMUCH) between January 2021 and June 2024, divided into RACS (n=82) and LCS (n=143) groups. Data on demographics, clinicopathological variables, surgical parameters, and perioperative outcomes were analyzed. Statistical significance was set at p < 0.05.ResultsRACS was associated with longer surgery durations (median: 218.5 vs. 165 minutes) and greater blood loss (median: 100 vs. 50 mL) compared to LCS (p < 0.001 for both). Additionally, the median hospitalization cost was notably higher for RACS at 117,822 RMB compared to 78,174 RMB for LCS (p < 0.0001). RACS was used more frequently for proctectomy (87.80% vs. 72.48%). No significant differences were found in lymph node dissection (LND), postoperative hospital stay, conversion to open surgery, or postoperative complications between the groups (p > 0.05). Anastomotic leakage was the most common complication in both groups (RACS: 3.66%, LCS: 4.20%), with no significant difference in incidence (p = 0.876). To reduce bias due to surgical site, cases of rectal and sigmoid colon cancer were singled out. Hierarchical analysis showed significant differences still remained in surgical duration, blood loss, and surgical site distribution for proctectomy and sigmoid colon resection (p < 0.001). RACS did not show a clear advantage in surgical field exposure or tissue retraction.ConclusionRACS, despite superior visualization, involved longer operative times and more blood loss than LCS. Both techniques had similar clinical outcomes, with LCS offering specific technical advantages.